Study on Potentiality of Biogas Plants and Their Role for the Conservation of Environment - Ghimire, Dinesh; Shrestha, Jagannath; K.C, Anup (Nepal Journal of Science and Technology, 2015)
This study presents the potentiality of biogas plants and their role for the conservation of environment. It is basedon primary data collected from 84 household surveys, 6 key informant interviews and two focus group discussions. It was observed that more than 95% of the people residing in the VDCs were using firewood as a main source ofenergy. The total amount of firewood consumed was 510.570 ton/year which emits 775.052tCO2e/year. Due to the presence of agriculture based livestock holding population, there is a great potential of biogas technology. Thestudy showed that biogas technology could saved 34.40% of firewood which conserves 5.415 ha of forests area. There is a potentiality of 58 biogas plants of size 6 cu.m which will reduce 440.800 tCO2e/year. DOI: http://dx.doi.org/njst.v15i2.12114 Nepal Journal of Science and Technology Vol. 15, No.2 (2014) 51-56